The Magic of Product Quality, Price, And Customer Satisfaction on Customer Loyalty - Andriana, Ririn; Witara, Ketut; Sri Lestari, Aprilia Winda (Universitas Prasetiya Mulya, 2024)
The primary objective of this study is to examine how productquality and price influence customer loyalty using customer satisfaction among Madame Gie Official Shop's Shopee consumers. The research methodology employed is quantitative to establish the significance of relationships between the variables under investigation. The population for this study consists of all customers of Madame Gie Official Shop on Shopee. The sample size is 100 individuals selected through purposive sampling.The respondents are females aged at least 17 years, who have made a minimum of 2 purchases on Madame Gie Official Shop's Shopee page. Data was collected using observation, questionnaires, analyzed through path analysis. Results show significant partial impacts of product quality and price on customer satisfaction and customer loyalty, with product quality and price affecting customer loyalty through customer satisfaction.